The Effect of Time Management and Self-Leadership on the Work Productivity of Generation Z among Freelance Student Workers at Universitas 17 Agustus 1945 Samarinda - Aulia Asyifa; Catur Kumala Dewi; Sukirman Sukirman (STMIK Widya Cipta Dharma, 2026)
The development of the digital economy has encouraged an increasing number of Generation Z students to engage in freelance work. This condition requires students to balance academic activities and work responsibilities in order to maintain productivity. The work productivity of freelance student workers is influenced by various factors, including time management and self-leadership. This study aims to analyze the effect of time management and self-leadership on the work productivity of Generation Z freelance student workers at Universitas 17 Agustus 1945 Samarinda. This research employed a quantitative approach using primary data collected through questionnaires and interviews. The population consisted of 1,484 students from the 2022 and 2023 cohorts, with a sample of 94 respondents selected through a purposive sampling technique. Data were analyzed using multiple linear regression with the assistance of Statistical Product and Service Solutions (SPSS). The results indicate that time management and self-leadership partially have a positive and significant effect on work productivity. Simultaneously, both variables also have a positive and significant effect on the work productivity of freelance student workers at Universitas 17 Agustus 1945 Samarinda. These findings suggest that the ability to manage time and lead oneself plays an important role in improving work productivity and supporting a balance between academic and work activities, enabling students to achieve work targets effectively and efficiently without neglecting their academic responsibilities.